Dinamika Penerapan Khilafah Sebuah Tinjauan Sosio-Historis - Henny Yusalia (Wardah, 2016)
Abstract: The idea of Islamic rule, commonly called the Khilafah Islamiyah, a controversy which almost endless. This form movement persists and even already in various countries. Khilafah Islamiyah era used to be an inspiration to form the Islamic system of government at this time. But it can not be denied also that in the context of the current modern state that has established administrative boundaries, by considering various things as forming the country, then the idea of the Khilafah Islamiyah in the form of cross-border state administrative problem. Variations understanding of the Khilafah Islamiyah, led to the adoption of this concept will always be at the limit mere ideals. The unification of perception and understanding, it is difficult to achieve because each human being has a variety of logical thinking. This paper is not the result of the study, but based in-depth study about the idea, and its reflection in the context of the modern state.